Quorum sensing-dependent post-secretional activation of extracellular proteases in Pseudomonas aeruginosa - Li, Xi-Hui (J Biol Chem, 2019)
Pseudomonas aeruginosa secretes multiple proteases that are implicated in its pathogenesis, and most of them are regulated by quorum sensing (QS). In this study, we found that the activities of three major extracellular proteases, protease IV (PIV), elastase A (LasA), and elastase B (LasB), are reduced considerably when expressed in a QS mutant (MW1). PIV and LasA expressed in MW1 exhibited little activity, even when purified, and their activities were inhibited by noncleavage or binding of their propeptides. LasB was activated by a QS-dependent factor, indicating that, unlike what has been proposed previously, LasB is not autoactivated. When LasB was relieved from inhibition, it activated PIV, which then sequentially processed pro-LasA to mature LasA. When activated, LasB was not inhibited by exogenous addition of its propeptide, but LasA and PIV were inhibited by their propeptides, even after prior activation. These differences may be explained by the fact that LasB can degrade its own propeptide but PIV and LasA cannot. We also found that, although PIV is the preferred LasA-activating factor, LasB can also partially activate LasA. Overall, LasB, PIV, and LasA were activated postsecretionally in a cascading manner in which the initial activation of LasB was controlled tightly by QS at the protein level in addition to the well-known transcriptional control of these proteases by QS. Interestingly, human elastase also activated LasA, indicating that the activation cascade is triggered by host factors during infection. In summary, a QS-induced proteolytic cascade activates secreted proteases from P. aeruginosa.